If it's not what You are looking for type in the equation solver your own equation and let us solve it.
1/3(9x+5)=5(x-1)-6
We simplify the equation to the form, which is simple to understand
1/3(9x+5)=5(x-1)-6
Simplifying:
+ 0.333333333333*(9x+5)=5*(x-1)-6
Reorder the terms in parentheses
+(+3x+1.66666666667)=5*(x-1)-6
Remove unnecessary parentheses
+3x+1.66666666667=+5+*(+x-1+)-6
Reorder the terms in parentheses
+3x+1.66666666667=+(+5x-5)-6
Remove unnecessary parentheses
+3x+1.66666666667=+5x-5-6
We move all terms containing x to the left and all other terms to the right.
+3x-5x=-5-6-1.66666666667
We simplify left and right side of the equation.
-2x=-12.6666666667
We divide both sides of the equation by -2 to get x.
x=6.33333333334
| 4b^2+(-7)b=0 | | 2a+6=a-8 | | f(x)=2x^2-5x-3 | | -3h+4.2=55-11h | | 6+(3x-3)=2 | | 3x+5-3x=4x-2 | | 3x+5-3x=4x-2 | | -10+p/9=-11 | | -9(x+6)=-54 | | 1/5s=2 | | 8x^2-22x-90=0 | | 7mx^2+2nx^2-7my^2-2ny^2=0 | | 7/5-3/8(136/15)=-2 | | 25+4(-4x+5)= | | 14z=0 | | 8/3x^2-5/4x | | 1/2x=11/14+4/7 | | 7/5-3/8(136/15) | | 17-(6x+3)-2x+4= | | ((3(x-4)/4)/4)=4x-4 | | 6a^2+27a-15=0 | | 7x+2y=26 | | 75/3*25= | | 10w-14wv-15w+21v=0 | | 3(x-8)=4(x+2) | | -2[6x+1]=4[x-5]-2 | | -12*(6-4)+2= | | (5/8)(-9) | | 3(x-8)=4x+2 | | -12*6-(4+2)= | | 8ax-6x-12a+9=0 | | 16x=1248 |